Experimental study of the impact of electrospinning parameters on the electromechanical properties of strain sensitive electrospun multiwalled carbon nanotubes/ thermoplastic polyurethane nanofibers - UZUN, MUHAMMET (TAYLOR & FRANCIS LTD, 2022)
Flexible strain sensitive electrospun fibrous layers have attracted widespread attention of researchers owing to their large surface area and exceptional flexibility. Herein, a detailed research on the impact of electrospinning parameters on the morphological and electromechanical properties of electrospun multiwalled carbon nanotubes (MWCNTs)/thermoplastic polyurethane (TPU) nanofibers is conducted. Besides the MWCNTs concentrations, electrospinning parameters have a significant effect on the morphology, electromechanical and sensory properties of electrospun MWCNTs/TPU nanofibrous membrane. Results show that at lower collector speeds, tip to collector distances, and higher electrospinning time lead to the formation of more homogeneously dispersed fibrous structures, which result in enhanced conductivity and strain sensitivity. Consequently, from the repeatability tests, all samples show quite similar linear responses under strain, indicating a highly repeatable fabrication process. Obtained results can help to gain a deeper understanding of the importance of controlling the electrospinning parameters, especially in the production of flexible strain sensors.
Keywords: multiwalled carbon nanotubes; thermoplastic polyurethane; electrospinning; nanofibers; strain sensing; piezoresistivity; SENSORS; PERFORMANCE; FILMS; NETWORK